Analisis Pengaruh Inflasi dan Pengangguran Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2014-2023 - Fitrawaty Fitrawaty; Fidia Wati; Rina Rina; Uswatul Akmalia (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the impact of inflation and unemployment on economic growth in Indonesia during the 2014-2023 period. The research uses secondary data sourced from the World Bank. The methodology employs a quantitative approach with multiple linear regression analysis. The results show that the research model explains 53.3% of the variation in economic growth. Inflation has a negative effect on economic growth with a significance level approaching 90%, while unemployment shows no significant effect. These findings indicate that controlling inflation plays an important role in driving Indonesia's economic growth, while the relationship between unemployment and economic growth requires further study considering other relevant factors.